Acetaminophen Intoxication Rapidly Induces Apoptosis of Intestinal Crypt Stem Cells and Enhances Intestinal Permeability. Issue 11 (15th July 2019) - Chopyk, Daniel M.; Stuart, Johnasha D.; Zimmerman, Matthew G.; Wen, Jing; Gumber, Sanjeev; Suthar, Mehul S.; Thapa, Manoj; Czaja, Mark J.; Grakoui, Arash
Abstract : Acetaminophen (APAP)‐induced liver injury is the most common cause of acute liver failure (ALF) in the Western world. APAP toxicity progresses to multiorgan dysfunction and thus has broader whole‐body implications. Importantly, greater 30‐day mortality has been observed in liver transplant recipients following ALF due to APAP‐related versus non‐APAP‐related causes. Reasons for this discrepancy have yet to be determined. Extrahepatic toxicities of APAP overdose may represent underappreciated and unaddressed comorbidities within this patient population. In the present study, rapid induction of apoptosis following APAP overdose was observed in the intestine, an organ that greatly influences the physiology of the liver. Strikingly, apoptotic cells appeared to be strictly restricted to the intestinal crypts. The use of leucine‐rich repeat‐containing G protein–coupled receptor 5 ( LGR5 ) reporter mice confirmed that the LGR5 ‐positive ( +) crypt base stem cells were disproportionately affected by APAP‐induced cell death. Although the apoptotic cells were cleared within 24 hours after APAP treatment, potentially long‐lived consequences on the intestine due to APAP exposure were indicated by prolonged deficits in gut barrier function. Moreover, small intestinal cell death was found to be independent of tumor necrosis factor receptor signaling and may represent a direct toxic insult to the intestine by exposure to high concentrations of APAP. Conclusion: APAP induces intestinal injury through a regulated process of apoptotic cell death that disproportionately affects LGR5 + stem cells. This work advances our understanding of the consequences of APAP toxicity in a novel organ that was not previously considered as a significant site of injury and thus presents potential new considerations for patient management. Abstract : In the present study, we present evidence that acute acetaminophen intoxication rapidly induces apoptosis within intestinal tissue independent of tumor necrosis factor receptor signaling. Strikingly, apoptosis was specifically limited to intestinal crypt stem cells, and thus results in potentially long‐lived consequences such as enhanced gut permeability. Our observations highlight additional extrahepatic toxicities of APAP overdose with implications on patient treatment and outcome.